DINAMIKA SOSIAL PESERTA DIDIK DAN PENDIDIKAN KARAKTER DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN - Ummu Kholifatul Khasanah; Rahmad Syahputra; Bansu Irianto Ansari; Putri Zaera, Sonia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education does not only function as a means of transferring academic knowledge but also as a social process that plays an important role in shaping students’ character and personality. Schools serve as social spaces where students learn to interact, adapt, and understand the values and norms prevailing in society. Social dynamics that occur within the school environment, particularly at the primary and secondary education levels, become a primary medium for the internalization of moral values, social attitudes, and the continuous development of students’ character. This article aims to examine students’ social dynamics and the role of character education from the perspective of the sociology of education. The research method employed is a literature review by analyzing various scientific journals, books, and relevant academic sources. The findings indicate that social interactions among students, the role of teachers as agents of socialization, school culture, and the integration of character education into the learning process make significant contributions to the development of students’ social, moral, and academic attitudes. Therefore, the sociology of education approach serves as an important foundation in designing education that is not only oriented toward academic achievement but also toward the holistic development of students’ character in accordance with societal needs.